Developing an ethical evaluation framework for coercive antimicrobial stewardship policies - Johnson, T (Oxford University Press, 2024)
Antimicrobial resistance (AMR) has been declared one of the top ten global public health threats facing humanity. To address AMR, coercive antimicrobial stewardship policies are being enacted in some settings. These policies, like all in public health, require ethical justification. Here, I introduce a framework for ethically evaluating coercive antimicrobial stewardship policies on the basis of ethical justifications (and their limitations). I consider arguments from effectiveness; duty of easy rescue; tragedy of the commons; responsibility-tracking; the harm principle; paternalism; justice and development; a precautionary approach; and professional duties. I consider how these justifications might form the basis for developing a comprehensive ethical framework, and the need for this to be context-specific and aligned with the priorities, evidence and needs of the particular jurisdictions in which a policy is to be enacted. I demonstrate how the ethical justifications might be used by reference to an example policy of the EU ban on the use of certain human-critical antibiotics for livestock, before concluding with challenges for further development of the framework.